Formation and thermal stability of two-phase microstructures in Al-containing refractory compositionally complex alloys - Stephan Laube; Alexander Kauffmann; Steven Schellert; Sascha Seils; Aditya Srinivasan Tirunilai; Christian Greiner; Yolita M. Eggeler; Bronislava Gorr; Hans-Juergen Christ; Martin Heilmaier (Science and Technology of Advanced Materials)
Phase separation into an A2+B2 two-phase microstructure in refractory compositionally complex alloys (RCCA) has been speculated as being spinodal in nature with continuous chemical distribution during the separation. However, these reactions might instead occur as precipitation by nucleation and growth. In order to unequivocally elucidate the distinct nature of phase separation sequence in RCCA from the system Ta-Mo-Ti-Cr-Al, atom probe tomography and electron microscopy techniques were utilized on samples that were annealed over multiple orders of magnitude in time. The composition 82(TaMoTi)-8Cr-10Al (at.%) was chosen, as it exhibits a two-phase microstructure, with a desired A2 matrix and embedded B2 phase. Quenching the samples from 1200°C resulted in a microstructure consisting of ordered clusters (2 nm) of distinct chemical composition. Subsequent annealing at 800°C to 1000°C leads to an increase in the volume fraction of the precipitating phase, which saturates after 10 h. Further annealing leads to the ripening of the microstructure; however, the absolute size of the precipitates stays <100 nm even after 1000 h. For the investigated conditions, the interface between matrix and precipitate can be considered sharp within the resolution of the applied techniques and no significant change in the transition of chemical composition across the interface is observed. Therefore, the phase separation mechanism is confirmed to be phase nucleation and growth in contrast to the possible spinodal decomposition, as hypothesized for other RCCA systems. The impact of precipitation and coarsening on the hardness of the alloy is discussed.